Technology in Irish literature and culture - Kelleher, Margaret 1964-; O'Sullivan, James 1986- (Cambridge University Press, 2023)
Technology in Irish Literature and Culture shows how such significant technologies-typewriters, gramophones, print, radio, television, computers-have influenced Irish literary practices and cultural production, while also examining how technology has been embraced as a theme in Irish writing. Once a largely rural and agrarian society, contemporary Ireland has embraced the communicative, performative and consumption habits of a culture utterly reliant on the digital. This text plumbs the origins of the present moment, examining the longer history of literature's interactions with the technological and exploring how the transformative capacity of modern technology has been mediated throughout a diverse national canon. Comprising essays from some of the major figures of Irish literary and cultural studies, this volume offers a wide-ranging, comprehensive account of how Irish literature and culture have interacted with technology